Regulation of the Drosophila Imd pathway by signaling amyloids. (May 2019) - Kleino, Anni; Silverman, Neal
Abstract: Fruit flies elicit effective defense responses against numerous microbes. The responses against Gram-negative bacteria are mediated by the Imd pathway, an evolutionarily conserved NF-κB pathway recognizing meso -diaminopimelic acid (DAP)-type peptidoglycan from bacterial cell walls. Several reviews already provide a detailed view of ligand recognition and signal transduction during Imd signaling, but the formation and regulation of the signaling complex immediately downstream of the peptidoglycan-sensing receptors is still elusive. In this review, we focus on the formation of the Imd amyloidal signaling center and post-translational modifications in the assembly and disassembly of the Imd signaling complex. Graphical abstract: Image 1 Highlights: In Drosophila, immune signaling through the Imd pathway is mediated by an amyloidal supramolecular organizing center (SMOC). Amyloid formation is dependent on cryptic RIP homotypic interaction motifs (cRHIMs) in PGRP-LC, PGRP-LE, and Imd. Post-translational modifications and Pirk regulate the disassembly of the amyloidal Imd SMOC.